CEO INFLUENCE AND FIRM PERFORMANCE: THE MEDIATING ROLE OF STRATEGIC RISK-TAKING IN AN EMERGING MARKET (Lex localis - Journal of Local Self-Government, 2025)
Whether and how Chief Executive Officers (CEOs) impact firm performance remains a central, unresolved debate in management research, marked by persistent empirical inconsistencies. This study contends that these conflicting findings stem from a conceptual failure to model the intermediate strategic decisions that transmit executive influence. The study posit that strategic risk-taking, operationalized as entrepreneurial risk (Capital Expenditures) and financial risk (Debt Ratio), constitutes the essential "missing link" connecting a CEO's demographic attributes to organizational performance. We test a comprehensive mediation model using a panel dataset of 280 non-financial firms listed on the Indonesia Stock Exchange (IDX) from 2010 to 2019. Our results reveal that the influence of CEO characteristics is predominantly indirect. Specifically, CEO age and education significantly predict firm performance through their influence on capital expenditures, while CEO gender and age operate via their impact on the firm's debt ratio. These findings significantly refine Upper Echelons Theory by moving beyond direct-effects models to elucidate the mechanisms of executive influence. We offer a more cohesive and causally specified framework for understanding the "CEO effect" within an emerging market's critical yet understudied context.